2009
DOI: 10.1055/s-0029-1223879
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Neurosurgery 2009: Review and Perspective

Abstract: In the treatment of psychiatric disorders, modern lesion procedures and nonablative deep brain stimulation (DBS) offer a degree of hope for patients who remain severely ill and impaired despite pharmacological and behavioral treatments. The available data support the therapeutic promise of these procedures, primarily for those suffering with obsessive-compulsive disorder (OCD) or major depressive disorder (MDD). However, the use of neurosurgical treatments for psychiatric disorders must be approached with both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…As Figure 4B shows, however, they do so in opposite directions. Rudebeck and Murray (91) compared performance one trial after an error (called trial E+1), one trial after an error-correct sequence (EC+1), one trial after an error-correct-correct sequence [EC(2)+1], and so forth. This analysis shows that PFo lesions cause an inefficiency in using positive feedback (blue asterisks in Fig.…”
Section: Prefrontal Cortex and Amygdala Function In Reversal Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…As Figure 4B shows, however, they do so in opposite directions. Rudebeck and Murray (91) compared performance one trial after an error (called trial E+1), one trial after an error-correct sequence (EC+1), one trial after an error-correct-correct sequence [EC(2)+1], and so forth. This analysis shows that PFo lesions cause an inefficiency in using positive feedback (blue asterisks in Fig.…”
Section: Prefrontal Cortex and Amygdala Function In Reversal Tasksmentioning
confidence: 99%
“…Even when successful, no one knows quite why. Examples of neurosurgical treatments for MDD include lesions in several structures: the frontal cortex beneath the genu of the corpus callosum, fiber tracts ventral to the caudate nucleus, the anterior part of the internal capsule, the prelimbic white matter, and the anterior cingulate cortex (1, 2). Localized deep brain stimulation has targeted the subgenual medial frontal cortex and the internal capsule (35).…”
Section: Introductionmentioning
confidence: 99%
“…BS is complicated by issues involving patient categorization and selection criteria, the long-term management of these patients, and the different patterns of potential benefits and burdens. [22] The Canadian Network for Mood and Anxiety Treatments (CANMAT) reviewed the role of neurostimulation including ECT, repetitive transcranial magnetic stimulation (rTMS), VNS, and DBS in MDD, and concluded that while there was good evidence for ECT as first-line treatment, some evidence for rTMS as second-line treatment, the evidence for VNS was less robust, and DBS remained experimental therapy. [15] Therefore, there is a need for stringent ethical, governance, and regulatory frameworks to be put in place in each legal jurisdiction in the world to prevent potential misuse of BS.…”
Section: Discussionmentioning
confidence: 99%
“…The OCD experience with DBS has been thoroughly reviewed elsewhere. 16,42 Importantly, the use of DBS for refractory OCD has been subjected to a double-blind randomized study, whose positive result indicates that the technology is indeed an effective form of last-resort treatment. 35 Such studies satisfy important criteria for the application of this technology to pediatric populations, where the threshold for surgical intervention is typically higher.…”
Section: Obsessive-compulsive Disordermentioning
confidence: 99%